YouTube Media in Increasing Student Interest in Dance Arts Learning - Ghaida, Regina; Budiman, Agus; Kurniati, Fitri; Yulia, Ulfa (Journal of Dance and Dance Education Studies, 2025)
As technology advances, learning media are needed to support classroom learning and increase student interest. This research, motivated by these challenges, focuses on utilizing YouTube as a learning medium to increase student interest in dance lessons. The purpose of this study was to determine the effectiveness of YouTube in dance lessons. Increase student learning interest. This study uses the classroom action research (CAR) method, conducted over 2 cycles, where each cycledone2 meetings with 4 stages, namely planning, implementation, observation, and reflection, instrument The method used in this study was a learning interest questionnaire. The population and sample used in this study were class VIII C at SMPN 1 Lembang with a total of 38 students. The results of the study showed that using YouTube media in class learning can be more effective in increasing students' learning interest, based on the results of the One-Sample T test, the results obtained a significance value of